Rule Based Mamdani Fuzzy Inference System to Analyze Efficacy of COVID19 Vaccines - Mittal, Poonam; Abirami, S P; Ramya, Puppala; J, Balajee; Muniyandy, Elangovan (EAI Endorsed Transactions on Pervasive Health and Technology, 2024)
INTRODUCTION: COVID-19 was declared as most dangerous disease and even after maintaining so many preventive measures, vaccination is the only preventive option from SARS-CoV-2. Vaccination has controlled the risk and spreading of virus that causes COVID-19. Vaccines can help in preventing serious illness and death. Before recommendation of COVID-19 vaccines, clinical experiments are being conducted with thousands of grown person and children. In controlled      situations like clinical trials, efficacy refers to how well a vaccination prevents symptomatic or asymptomatic illness.OBJECTIVES: The effectiveness of a vaccine relates to how effectively it works in the actual world.METHODS: This research presents a novel approach to model the efficacy of COVID’19 vaccines based on Mamdani Fuzzy system Modelling. The proposed fuzzy model aims to gauge the impact of epidemiological and clinical factors on which the efficacy of COVID’19 vaccines.RESULTS: In this study, 8 different aspects are considered, which are classified as efficiency evaluating factors. To prepare this model, data has been accumulated from various research papers, reliable news articles on vaccine response in multiple regions, published journals etc.   A set of Fuzzy rules was inferred based on classified parameters. This fuzzy inference system is expected to be of great help in recommending the most appropriate vaccine on the basis of several parameters. CONCLUSION: It aims to give an idea to pharmaceutical manufacturers on how they can improve vaccine efficacy and for the decision making that which one to be followed.
Keywords: Covid19; Covid19 Vaccines; Side-Effects; Demographic Factors; Efficacy of Covid Vaccines; Medical History; Fuzzy Inference System; Mandani Fuzzy Model